A direct In Vivo RNAi screen identifies MKK4 as a key regulator of liver regeneration - Wüstefeld, Torsten; Longerich, Thomas; Schirmacher, Peter (Cell, 2013)
The liver harbors a distinct capacity for endogenous regeneration; however, liver regeneration is often impaired in disease and therefore insufficient to compensate for the loss of hepatocytes and organ function. Here we describe a functional genetic approach for the identification of gene targets that can be exploited to increase the regenerative capacity of hepatocytes. Pools of small hairpin RNAs (shRNAs) were directly and stably delivered into mouse livers to screen for genes modulating liver regeneration. Our studies identify the dual-specific kinase MKK4 as a master regulator of liver regeneration. MKK4 silencing robustly increased the regenerative capacity of hepatocytes in mouse models of liver regeneration and acute and chronic liver failure. Mechanistically, induction of MKK7 and a JNK1-dependent activation of the AP1 transcription factor ATF2 and the Ets factor ELK1 are crucial for increased regeneration of hepatocytes with MKK4 silencing.